Functional-State Dependence of Picosecond Protein Dynamics - George, D. K.; Chen, J. Y.; He, Yunfen; Knab, J. R.; Markelz, A. G. (J. Phys. Chem. B, 2021)
We examine temperature-dependent picosecond dynamics of two benchmarking proteins lysozyme and cytochrome c using temperature-dependent terahertz permittivity measurements. We find that a double Arrhenius temperature dependence with activation energies E1 ∼ 0.1 kJ/mol and E2 ∼ 10 kJ/mol fits the folded and ligand-free state response. The higher activation energy is consistent with the so-called protein dynamical transition associated with beta relaxations at the solvent–protein interface. The lower activation energy is consistent with correlated structural motions. When the structure is removed by denaturing, the lower-activation-energy process is no longer present. Additionally, the lower-activation-energy process is diminished with ligand binding but not for changes in the internal oxidation state. We suggest that the lower-energy activation process is associated with collective structural motions that are no longer accessible with denaturing or binding.

The 2017 terahertz science and technology roadmap - Dhillon, S. S.; Vitiello, M. S.; Linfield, E. H.; Davies, A. G.; Hoffmann, M. C.; Booske, J.; Paoloni, C.; Gensch, M.; Weightman, P.; Williams, G. P.; Castro-Camus, E.; Cumming, D. R. S.; et al. (Journal of Physics D-Applied Physics, 2017)
Science and technologies based on terahertz frequency electromagnetic radiation (100 GHz-30 THz) have developed rapidly over the last 30 years. For most of the 20th Century, terahertz radiation, then referred to as sub-millimeter wave or far-infrared radiation, was mainly utilized by astronomers and some spectroscopists. Following the development of laser based terahertz time-domain spectroscopy in the 1980s and 1990s the field of THz science and technology expanded rapidly, to the extent that it now touches many areas from fundamental science to 'real world' applications. For example THz radiation is being used to optimize materials for new solar cells, and may also be a key technology for the next generation of airport security scanners. While the field was emerging it was possible to keep track of all new developments, however now the field has grown so much that it is increasingly difficult to follow the diverse range of new discoveries and applications that are appearing. At this point in time, when the field of THz science and technology is moving from an emerging to a more established and interdisciplinary field, it is apt to present a roadmap to help identify the breadth and future directions of the field. The aim of this roadmap is to present a snapshot of the present state of THz science and technology in 2017, and provide an opinion on the challenges and opportunities that the future holds. To be able to achieve this aim, we have invited a group of international experts to write 18 sections that cover most of the key areas of THz science and technology. We hope that The 2017 Roadmap on THz science and technology will prove to be a useful resource by providing a wide ranging introduction to the capabilities of THz radiation for those outside or just entering the field as well as providing perspective and breadth for those who are well established. We also feel that this review should serve as a useful guide for government and funding agencies.
ISI Document Delivery No.: EI0HL Times Cited: 541 Cited Reference Count: 209 Cited References: Adam AJL, 2011, J INFRARED MILLIM TE, V32, P976, DOI 10.1007/s10762-011-9809-2 Ahmed SS, 2012, IEEE MICROW MAG, V13, P26, DOI 10.1109/MMM.2012.2205772 Alliance N., 2015, CISC VIS NETW IND GL, P1 [Anonymous], 2013, 178512012 IEEE [Anonymous], 2014, IEEE T ELECT DEVICES, V61 [Anonymous], 2012, 178522016 IEEE [Anonymous], 2015, P17852 IEEE Appleby R, 2015, P SOC PHOTO-OPT INS, V9462 Arnone DD, 1999, PROC SPIE, V3828, P209, DOI 10.1117/12.361037 Ashworth PC, 2009, OPT EXPRESS, V17, P12444, DOI 10.1364/OE.17.012444 AUSTON DH, 1988, IEEE J QUANTUM ELECT, V24, P184, DOI 10.1109/3.114 Barbieri S, 2011, NAT PHOTONICS, V5, P306, DOI [10.1038/NPHOTON.2011.49, 10.1038/nphoton.2011.49] Barker RJ., 2005, MODERN MICROWAVE MIL Basov DN, 2011, REV MOD PHYS, V83, P471, DOI 10.1103/RevModPhys.83.471 Bauwens M. F., 2014, P IEEEMTT S INT MICR, P1, DOI [10.1109/MWSYM.2014.68486 07, DOI 10.1109/MWSYM.2014.6848607] Beard MC, 2002, NANO LETT, V2, P983, DOI 10.1021/nl0256210 Beard MC, 2000, PHYS REV B, V62, P15764, DOI 10.1103/PhysRevB.62.15764 Bechtel HA, 2014, P NATL ACAD SCI USA, V111, P7191, DOI 10.1073/pnas.1400502111 Belkin MA, 2008, OPT EXPRESS, V16, P3242, DOI 10.1364/OE.16.003242 Belkin MA, 2015, PHYS SCRIPTA, V90, DOI 10.1088/0031-8949/90/11/118002 Bell R., 2012, INTRO FOURIER TRANSF Berry CW, 2013, NAT COMMUN, V4, DOI 10.1038/ncomms2638 Blanchard F, 2011, OPT EXPRESS, V19, P8277, DOI 10.1364/OE.19.008277 Blau J, 2013, P FREE EL LAS FEL 20, P486 Booske JH, 2011, IEEE T THZ SCI TECHN, V1, P54, DOI 10.1109/TTHZ.2011.2151610 Booske JH, 2008, PHYS PLASMAS, V15, DOI 10.1063/1.2838240 Boppel S, 2012, 2012 IEEE 12TH TOPICAL MEETING ON SILICON MONOLITHIC INTEGRATED CIRCUITS IN RF SYSTEMS (SIRF), P77, DOI 10.1109/SiRF.2012.6160142 Burghoff D, 2014, NAT PHOTONICS, V8, P462, DOI 10.1038/nphoton.2014.85 Busch SF, 2014, J INFRARED MILLIM TE, V35, P993, DOI 10.1007/s10762-014-0113-9 Byrne MB, 2011, APPL PHYS LETT, V98, DOI 10.1063/1.3579258 Carr GL, 2002, NATURE, V420, P153, DOI 10.1038/nature01175 Carranza IE, 2015, IEEE T THZ SCI TECHN, V5, P892, DOI 10.1109/TTHZ.2015.2463673 Castro-Camus E, 2007, OPT EXPRESS, V15, P7047, DOI 10.1364/OE.15.007047 Chan WL, 2007, REP PROG PHYS, V70, P1325, DOI 10.1088/0034-4885/70/8/R02 Chattopadhyay G, 2011, IEEE T THZ SCI TECHN, V1, P33, DOI 10.1109/TTHZ.2011.2159561 Chen HT, 2003, APPL PHYS LETT, V83, P3009, DOI 10.1063/1.1616668 Chen JN, 2012, NATURE, V487, P77, DOI 10.1038/nature11254 Cocker T L, 2016, J PHYS D, V16, P1421 Cocker TL, 2013, NAT PHOTONICS, V7, P620, DOI [10.1038/NPHOTON.2013.151, 10.1038/nphoton.2013.151] Coleman B, 2001, Issue Brief (Public Policy Inst (Am Assoc Retired Pers)), P1 Cooper KB, 2014, IEEE MICROW MAG, V15, P51, DOI 10.1109/MMM.2014.2356092 Cruz F C, 2007, C MICR OPT Cunningham J, 2010, ELECTRON LETT, V46, pS34, DOI 10.1049/el.2010.3317 Dean P, 2011, OPT LETT, V36, P2587, DOI 10.1364/OL.36.002587 Dietz RJB, 2014, OPT LETT, V39, P6482, DOI 10.1364/OL.39.006482 Dietz RJB, 2014, OPT EXPRESS, V22, P19411, DOI 10.1364/OE.22.019411 Dobrovolsky V, 2007, SEMICOND SCI TECH, V22, P103, DOI 10.1088/0268-1242/22/2/017 Ducournau G, 2014, IEEE T THZ SCI TECHN, V4, P328, DOI 10.1109/TTHZ.2014.2309006 Dunsmore J.P., 2012, HDB MICROWAVE COMPON Duvillaret L, 1999, APPL OPTICS, V38, P409, DOI 10.1364/AO.38.000409 Eisele M, 2014, NAT PHOTONICS, V8, P841, DOI [10.1038/nphoton.2014.225, 10.1038/NPHOTON.2014.225] Falconer RJ, 2012, J INFRARED MILLIM TE, V33, P973, DOI 10.1007/s10762-012-9915-9 Fathololoumi S, 2012, OPT EXPRESS, V20, P3866, DOI 10.1364/OE.20.003866 Fausti D, 2011, SCIENCE, V331, P189, DOI 10.1126/science.1197294 Federici J, 2010, J APPL PHYS, V107, DOI 10.1063/1.3386413 Fei Z, 2012, NATURE, V487, P82, DOI 10.1038/nature11253 FETTERMAN HR, 1974, APPL PHYS LETT, V24, P70, DOI 10.1063/1.1655098 Freeman JR, 2013, OPT EXPRESS, V21, P16162, DOI 10.1364/OE.21.016162 Frisk U, 2003, ASTRON ASTROPHYS, V402, pL27, DOI 10.1051/0004-6361:20030335 Garet F, 2014, APPL PHYS LETT, V105, DOI 10.1063/1.4890732 Gavrilov NG, 2007, NUCL INSTRUM METH A, V575, P54, DOI 10.1016/j.nima.2007.01.023 Gensch M., 2013, P 35 INT FREE EL LAS, P474 George DK, 2012, J OPT SOC AM B, V29, P1406, DOI 10.1364/JOSAB.29.001406 Giliberti V, 2013, APPL PHYS LETT, V103, DOI 10.1063/1.4819734 Grant J, 2013, LASER PHOTONICS REV, V7, P1043, DOI 10.1002/lpor.201300087 Green B, 2016, SCI REP-UK, V6, DOI 10.1038/srep22256 Griffith P.R., 2007, FOURIER TRANSFORM IN GRISCHKOWSKY D, 1990, J OPT SOC AM B, V7, P2006, DOI 10.1364/JOSAB.7.002006 Gruene P, 2008, SCIENCE, V321, P674, DOI 10.1126/science.1161166 Han NR, 2014, OPT LETT, V39, P3480, DOI 10.1364/OL.39.003480 Han RN, 2013, IEEE J SOLID-ST CIRC, V48, P2296, DOI 10.1109/JSSC.2013.2269856 Hanham SM, 2015, APPL PHYS LETT, V107, DOI 10.1063/1.4927242 Hassel J, 2015, PROC SPIE, V9651, DOI 10.1117/12.2197522 Hauri CP, 2011, APPL PHYS LETT, V99, DOI 10.1063/1.3655331 He W, 2015, APPL PHYS LETT, V107, DOI 10.1063/1.4932099 Hebling J, 2002, OPT EXPRESS, V10, P1161, DOI 10.1364/OE.10.001161 Heinz E, 2015, J INFRARED MILLIM TE, V36, P879, DOI 10.1007/s10762-015-0170-8 Henry SC, 2012, OPT ENG, V51, DOI 10.1117/1.OE.51.9.091603 Hesler J L, 2006, P 7 INT S SPAC TER T, P215 Hintzsche H, 2012, CRIT REV ENV SCI TEC, V42, P2408, DOI 10.1080/10643389.2011.574206 Hishida M, 2011, PHYS REV LETT, V106, DOI 10.1103/PhysRevLett.106.158102 Ho IC, 2010, OPT EXPRESS, V18, P2872, DOI 10.1364/OE.18.002872 HU BB, 1995, OPT LETT, V20, P1716, DOI 10.1364/OL.20.001716 Huang C, 2012, PHYS REV B, V85 Huber R, 2001, NATURE, V414, P286, DOI 10.1038/35104522 Jankowiak A., 2013, Synchrotron Radiation News, V26, P22, DOI 10.1080/08940886.2013.791212 Jepsen PU, 2007, CHEM PHYS LETT, V442, P275, DOI 10.1016/j.cplett.2007.05.112 Jepsen PU, 2011, LASER PHOTONICS REV, V5, P124, DOI 10.1002/lpor.201000011 Jepsen PU, 2005, OPT LETT, V30, P29, DOI 10.1364/OL.30.000029 JUICE-Jupiter Icy Moons Explorer, 2014, SRE20141 JUICE EUR S, P1 Kallfass I, 2011, IEEE T THZ SCI TECHN, V1, P477, DOI 10.1109/TTHZ.2011.2160021 Kampfrath T, 2013, NAT PHOTONICS, V7, P680, DOI [10.1038/nphoton.2013.184, 10.1038/NPHOTON.2013.184] Kan T, 2015, NAT COMMUN, V6, DOI 10.1038/ncomms9422 Karpowicz N, 2008, APPL PHYS LETT, V92, DOI 10.1063/1.2828709 Kehr SC, 2008, PHYS REV LETT, V100, DOI 10.1103/PhysRevLett.100.256403 Kemp MC, 2011, IEEE T THZ SCI TECHN, V1, P282, DOI 10.1109/TTHZ.2011.2159647 Khalid A, 2014, J APPL PHYS, V115, DOI 10.1063/1.4868705 Kirley MP, 2015, IEEE T THZ SCI TECHN, V5, P1012, DOI 10.1109/TTHZ.2015.2468074 Kiwa T, 2003, OPT LETT, V28, P2058, DOI 10.1364/OL.28.002058 Koch M, 2001, NATO SCI SER II MATH, V27, P241 Koenig S, 2013, NAT PHOTONICS, V7, P977, DOI [10.1038/nphoton.2013.275, 10.1038/NPHOTON.2013.275] Kohler R, 2002, NATURE, V417, P156, DOI 10.1038/417156a Koppens FHL, 2014, NAT NANOTECHNOL, V9, P780, DOI [10.1038/nnano.2014.215, 10.1038/NNANO.2014.215] Kosarev A, 2010, SOLID STATE ELECTRON, V54, P417, DOI 10.1016/j.sse.2009.12.032 Kundu I, 2014, OPT EXPRESS, V22, P16595, DOI 10.1364/OE.22.016595 Kuznetsov SA, 2010, KEY ENG MATER, V437, P276, DOI 10.4028/www.scientific.net/KEM.437.276 Langevin Y, 2005, PAYLOAD MISSION DEFI LaRue JL, 2015, PHYS REV LETT, V115, DOI 10.1103/PhysRevLett.115.036103 Leitenstorfer A, 2014, NEW J PHYS, V16, DOI 10.1088/1367-2630/16/4/045016 Leitner DM, 2006, INT REV PHYS CHEM, V25, P553, DOI 10.1080/01442350600862117 Li LH, 2014, ELECTRON LETT, V50, P309, DOI 10.1049/el.2013.4035 Liu L, 2010, IEEE MICROW WIREL CO, V20, P504, DOI 10.1109/LMWC.2010.2055553 Liu SC, 2016, OPT EXPRESS, V24, P2728, DOI 10.1364/OE.24.002728 Lu X H, 2008, P SOC PHOTO-OPT INS, V7277 Luukanen A, 2003, APPL PHYS LETT, V82, P3970, DOI 10.1063/1.1579562 Mann C, 2009, P SOC PHOTO-OPT INS, V7311, P3970 Mickan S, 2004, PROC SPIE, V5277, P54, DOI 10.1117/12.530386 Mineo M, 2010, IEEE T ELECTRON DEV, V57, P3169, DOI 10.1109/TED.2010.2071876 Mittleman DM, 1996, IEEE J SEL TOP QUANT, V2, P679, DOI 10.1109/2944.571768 Mittleman DM, 1999, APPL PHYS B-LASERS O, V68, P1085, DOI 10.1007/s003400050750 Moon K, 2012, APPL PHYS LETT, V101, DOI 10.1063/1.4733475 Muller AS, 2010, REV ACCEL SCI TECH, V3, P165, DOI 10.1142/S1793626810000427 Muller R, 2015, J INFRARED MILLIM TE, V36, P654, DOI 10.1007/s10762-015-0163-7 Naftaly M, 2015, TERAHERTZ METROLOGY, P1 Nagai M, 2015, OPT EXPRESS, V23, P4641, DOI 10.1364/OE.23.004641 Nagatsuma T, 2012, OPT EXPRESS, V21, P477 Nagel M, 2002, APPL PHYS LETT, V80, P154, DOI 10.1063/1.1428619 Navarro-Cia M, 2015, J INFRARED MILLIM TE, V36, P542, DOI 10.1007/s10762-015-0157-5 Nielsen K, 2009, OPT EXPRESS, V17, P8592, DOI 10.1364/OE.17.008592 Niessen Katherine A, 2015, Biophys Rev, V7, P201, DOI 10.1007/s12551-015-0168-4 Nordquist CD, 2011, IEEE J SEL TOP QUANT, V17, P130, DOI 10.1109/JSTQE.2010.2049095 Oh SJ, 2012, J INFRARED MILLIM TE, V33, P74, DOI 10.1007/s10762-011-9847-9 Ojefors E, 2009, IEEE J SOLID-ST CIRC, V44, P1968, DOI 10.1109/JSSC.2009.2021911 Ortolani M, 2008, PHYS REV LETT, V97 Ozerov M, 2014, PHYS REV LETT, V113, DOI 10.1103/PhysRevLett.113.157205 Paoloni C, 2013, IEEE T ELECTRON DEV, V60, P1236, DOI 10.1109/TED.2013.2240686 Parrott EPJ, 2015, APPL SPECTROSC, V69, P1, DOI 10.1366/14-07707 Patrashin M, 2015, IEEE T ELECTRON DEV, V62, P1068, DOI 10.1109/TED.2015.2393358 Peiponen K. E., 2013, TERAHERTZ SPECTROSCO, V171 Peng K, 2015, NANO LETT, V15, P206, DOI 10.1021/nl5033843 Pickwell E, 2004, APPL PHYS LETT, V84, P2190, DOI 10.1063/1.1688448 Ponnampalam L, 2011, J LIGHTWAVE TECHNOL, V29, P2229, DOI 10.1109/JLT.2011.2158186 Pupeza I, 2007, OPT EXPRESS, V15, P4335, DOI 10.1364/OE.15.004335 Rauter P, 2015, LASER PHOTONICS REV, V9, P452, DOI 10.1002/lpor.201500095 Reid CB, 2011, PHYS MED BIOL, V56, P4333, DOI 10.1088/0031-9155/56/14/008 Reid J R, 2012, IEEE 12 TOP M SIL MO, P17 Rosch M, 2015, NAT PHOTONICS, V9, P42, DOI [10.1038/nphoton.2014.279, 10.1038/NPHOTON.2014.279] Rudd JV, 2000, PROC SPIE, V3934, P27, DOI 10.1117/12.386344 Rymanov V, 2015, PHOTONICS, V2, DOI 10.3390/photonics2041152 SANTOS Daisy Conceicao, 2014, THESIS Scherger B, 2011, APPL OPTICS, V50, P2256, DOI 10.1364/AO.50.002256 Schleicher JM, 2009, J APPL PHYS, V105, DOI 10.1063/1.3133093 Schumann S, 2012, OPT EXPRESS, V20, P19200, DOI 10.1364/OE.20.019200 Seeds AJ, 2015, J LIGHTWAVE TECHNOL, V33, P579, DOI 10.1109/JLT.2014.2355137 Sell A, 2008, OPT LETT, V33, P2767, DOI 10.1364/OL.33.002767 Shams H, 2015, IEEE PHOTONICS J, V7, DOI 10.1109/JPHOT.2015.2438437 Shams H, 2014, OPT EXPRESS, V22, P23465, DOI 10.1364/OE.22.023465 Shen YC, 2004, APPL PHYS LETT, V85, P164, DOI 10.1063/1.1768313 Simoens F., 2014, PHILOS T A, V372, P1 Simoens F, 2011, 36 INT C INFR MILL T, P1 Singh A, 2015, OPT EXPRESS, V23, P6656, DOI 10.1364/OE.23.006656 Sirtori C, 2013, NAT PHOTONICS, V7, P691, DOI [10.1038/NPHOTON.2013.208, 10.1038/nphoton.2013.208] SMITH PR, 1988, IEEE J QUANTUM ELECT, V24, P255, DOI 10.1109/3.121 Son JH, 2013, NANOTECHNOLOGY, V24, DOI 10.1088/0957-4484/24/21/214001 Swinyard B, 2013, SPIE SENSORS SYSTEMS Sy S, 2010, PHYS MED BIOL, V55, P7587, DOI 10.1088/0031-9155/55/24/013 Taylor ZD, 2015, IEEE T THZ SCI TECHN, V5, P184, DOI 10.1109/TTHZ.2015.2392628 Teppati V, 2013, CAMB RF MICROW ENG, P1, DOI 10.1017/CBO9781139567626 Tewari P, 2012, P SPIE, V8261 Thomas B., 2014, P 39 INT C INFR MILL, P1 Thumm M, 2014, KIT SCI REPORTS, V7693 Tonouchi M, 2007, NAT PHOTONICS, V1, P97, DOI 10.1038/nphoton.2007.3 Truong BCQ, 2015, IEEE T BIO-MED ENG, V62, P699, DOI 10.1109/TBME.2014.2364025 Turcinkova D, 2015, APPL PHYS LETT, V106, DOI 10.1063/1.4916653 Turner GM, 2002, J PHYS CHEM B, V106, P11716, DOI 10.1021/jp025844e van der Valk NCJ, 2002, APPL PHYS LETT, V81, P1558, DOI 10.1063/1.1503404 van Dijk F, 2014, IEEE PHOTONIC TECH L, V26, P965, DOI 10.1109/LPT.2014.2309353 Vicario C, 2014, PHYS REV LETT, V112, DOI 10.1103/PhysRevLett.112.213901 Vinh NQ, 2015, J CHEM PHYS, V142, DOI 10.1063/1.4918708 Vitiello MS, 2012, NAT PHOTONICS, V6, P525, DOI 10.1038/nphoton.2012.145 Vitiello MS, 2015, OPT EXPRESS, V23, P5167, DOI 10.1364/OE.23.005167 Vitiello MS, 2014, NAT COMMUN, V5, DOI 10.1038/ncomms6884 Wade A, 2009, NAT PHOTONICS, V3, P41, DOI 10.1038/NPHOTON.2008.251 Wallace B., 2015, SPIE NEWSROOM, DOI [10.1117/2.1201503.005871, DOI 10.1117/2.1201503.005871] Wallace VP, 2004, BRIT J DERMATOL, V151, P424, DOI 10.1111/j.1365-2133.2004.06129.x Wang FH, 2015, OPTICA, V2, P944, DOI 10.1364/OPTICA.2.000944 Weightman P, 2012, PHYS BIOL, V9, DOI 10.1088/1478-3975/9/5/053001 Wienold M, 2014, OPT EXPRESS, V22, P3334, DOI 10.1364/OE.22.003334 Wilk R, 2007, C LAS EL BALT MD Williams BS, 2006, ELECTRON LETT, V42, P89, DOI 10.1049/el:20063921 Williams GP, 2006, REP PROG PHYS, V69, P301, DOI 10.1088/0034-4885/69/2/R01 Williams GP, 2008, NAT PHYS, V4, P356, DOI 10.1038/nphys958 Williams MRC, 2013, J PHYS CHEM B, V117, P10444, DOI 10.1021/jp406730a Williams R, 2013, PHYS MED BIOL, V58, P373, DOI 10.1088/0031-9155/58/2/373 Withayachumnankul W, 2008, J OPT SOC AM B, V25, P1059, DOI 10.1364/JOSAB.25.001059 Woerner M, 2013, NEW J PHYS, V15, DOI 10.1088/1367-2630/15/2/025039 Woodward RM, 2003, J INVEST DERMATOL, V120, P72, DOI 10.1046/j.1523-1747.2003.12013.x Wu X, OPT LETT, V39, P5403 Wu ZR, 2013, REV SCI INSTRUM, V84, DOI 10.1063/1.4790427 Xu J, 2003, PROC SPIE, V5268, P19, DOI 10.1117/12.518533 Yamashita M, 2011, OPT EXPRESS, V19, P10864, DOI 10.1364/OE.19.010864 Yan F, 2013, J INFRARED MILLIM TE, V34, P489, DOI 10.1007/s10762-013-0005-4 Yang SH, 2014, IEEE T THZ SCI TECHN, V4, P575, DOI 10.1109/TTHZ.2014.2342505 Yeh KL, 2007, APPL PHYS LETT, V90, DOI 10.1063/1.2734374 Zamora A, 2015, IEEE MTT S INT MICR Zhao JF, 2011, IEEE T ELECTRON DEV, V58, P1221, DOI 10.1109/TED.2011.2109723 Zheludev NI, 2012, NAT MATER, V11, P917, DOI [10.1038/NMAT3431, 10.1038/nmat3431] Zhou Y, 2010, PROG ELECTROMAGN RES, V105, P71, DOI 10.2528/PIER10041806 Zibik EA, 2009, NAT MATER, V8, P803, DOI [10.1038/nmat2511, 10.1038/NMAT2511] Dhillon, S. S. Vitiello, M. S. Linfield, E. H. Davies, A. G. Hoffmann, Matthias C. Booske, John Paoloni, Claudio Gensch, M. Weightman, P. Williams, G. P. Castro-Camus, E. Cumming, D. R. S. Simoens, F. Escorcia-Carranza, I. Grant, J. Lucyszyn, Stepan Kuwata-Gonokami, Makoto Konishi, Kuniaki Koch, Martin Schmuttenmaer, Charles A. Cocker, Tyler L. Huber, Rupert Markelz, A. G. Taylor, Z. D. Wallace, Vincent P. Zeitler, J. Axel Sibik, Juraj Korter, Timothy M. Ellison, B. Rea, S. Goldsmith, P. Cooper, Ken B. Appleby, Roger Pardo, D. Huggard, P. G. Krozer, V. Shams, Haymen Fice, Martyn Renaud, Cyril Seeds, Alwyn Stoehr, Andreas Naftaly, Mira Ridler, Nick Clarke, Roland Cunningham, John E. Johnston, Michael B. Huggard, Peter/U-2150-2019; Konishi, Kuniaki/AAN-3624-2020; Zeitler, J. Axel/B-4885-2008; Paoloni, Claudio/AAH-9824-2019; Hoffmann, Matthias C./N-1082-2019; Wallace, Vincent P/A-9320-2012; Johnston, Michael/B-9813-2008; Castro-Camus, Enrique/V-6861-2019; Krozer, Viktor/P-5623-2014; Hoffmann, Matthias C/B-3893-2009; PAOLONI, CLAUDIO/AAA-3211-2020; Gonokami, Makoto/F-3641-2012; Shams, Haymen/H-3754-2012; Ridler, Nick/AAN-9637-2020; Huber, Rupert/N-4126-2018 Konishi, Kuniaki/0000-0003-2389-9787; Zeitler, J. Axel/0000-0002-4958-0582; Hoffmann, Matthias C./0000-0002-3596-9853; Wallace, Vincent P/0000-0003-3814-5400; Johnston, Michael/0000-0002-0301-8033; Krozer, Viktor/0000-0002-2387-1947; Hoffmann, Matthias C/0000-0002-3596-9853; PAOLONI, CLAUDIO/0000-0002-0265-0862; Shams, Haymen/0000-0002-5333-6478; Huber, Rupert/0000-0001-6617-9283; Davies, Alexander/0000-0002-1987-4846; Seeds, Alwyn/0000-0002-5228-627X; Castro-Camus, Enrique/0000-0002-8218-9155; Cunningham, John/0000-0002-1805-9743; Naftaly, Mira/0000-0002-0671-822X; Cumming, David/0000-0002-7838-8362 Engineering and Physical Sciences Research CouncilUK Research & Innovation (UKRI)Engineering & Physical Sciences Research Council (EPSRC) [EP/P015883/1, EP/M00306X/1, EP/K023349/1, EP/M017095/1, EP/L026597/1, EP/J017671/1] Funding Source: researchfish; Natural Environment Research CouncilUK Research & Innovation (UKRI)NERC Natural Environment Research Council [NER/Z/S/2003/00642, NE/L012375/1, NER/Z/S/2000/01292] Funding Source: researchfish; Science and Technology Facilities CouncilUK Research & Innovation (UKRI)Science & Technology Facilities Council (STFC) [ST/P002056/1] Funding Source: researchfish; Direct For Biological SciencesNational Science Foundation (NSF)NSF - Directorate for Biological Sciences (BIO) [1556359] Funding Source: National Science Foundation; Div Of Biological InfrastructureNational Science Foundation (NSF)NSF - Directorate for Biological Sciences (BIO) [1556359] Funding Source: National Science Foundation; Div Of Molecular and Cellular BioscienceNational Science Foundation (NSF)NSF - Directorate for Biological Sciences (BIO) [1616529] Funding Source: National Science Foundation 566 30 462 Iop publishing ltd Bristol 1361-6463
Keywords: ex-vivo; generation; metal wave-guides; near-field; performance; photoconductive emitters; Physics; quantum-cascade lasers; radiation; semiconductors; Terahertz; thz; time-domain spectroscopy

Photoactive yellow protein terahertz response: hydration, heating and intermediate states - George, Deepu K; Knab, Joseph R; He, Yunfen; Kumauchi, Masato; Birge, Robert R; Hoff, Wouter D; Markelz, Andrea G (IEEE Transactions on Terahertz Science and Technology, 2013)

Functional State Dependence of Picosecond Protein Dynamics - Chen, J. Y.; George, D. K.; He, Y.; Knab, J. R.; Markelz, A.G. (arXiv:1105.4425, 2012)

Evidence of protein collective motions on the picosecond timescale - He, Yunfen; Chen, J-Y; Knab, Joseph R; Zheng, Wenjun; Markelz, Andrea G (Biophysical Journal, 2011)

Why is THz Sensitive to Protein Functional States? Oxidation State of Cytochrome C - He,Y.; Chen, J.-Y.; Knab, J. R.; Zheng, W.; Markelz, A.G. (Terahertz Science and Technology, 2010)
We investigate the presence of structural collective motions on a picosecond time scale for the heme protein, cytochrome c, as a function of oxidation and hydration, using terahertz (THz) time-domain spectroscopy and molecular dynamics simulations. Structural collective mode frequencies have been calculated to lie in this frequency range, and the density of states can be considered a measure of flexibility. A dramatic increase in the THz response occurs with oxidation, with the largest increase for lowest hydrations and highest frequencies. For both oxidation states the measured THz response rapidly increases with hydration saturating above ~25% (g H2O/g protein), in contrast to the rapid turn-on in dynamics observed at this hydration level for other proteins. Quasi-harmonic collective vibrational modes and dipole-dipole correlation functions are calculated from the molecular dynamics trajectories. The collective mode density of states alone reproduces the measured hydration dependence providing strong evidence of the existence of these collective motions. The large oxidation dependence is reproduced only by the dipole-dipole correlation function, indicating the contrast arises from diffusive motions consistent with structural changes occurring in the vicinity of a buried internal water molecule.

The role of the protein surface on the local biological water dynamics - Liang, W.; He, Y. F.; George, D.; Markelz, A. G. (Biosensing Ii, 2009)
Protein function is reliant on structural flexibility and this flexibility is slaved to the surrounding solvent. Here we discuss how the exposed surface of the protein influences the solvent dynamics and thereby influences the protein's own structural dynamics. We discuss measurements of the THz absorption of water in the presence of hydrophilic and hydrophobic surfaces.
ISI Document Delivery No.: BVQ85 Times Cited: 0 Cited Reference Count: 12 Cited References: Balu R, 2008, BIOPHYS J, V94, P3217, DOI 10.1529/biophysj.107.105163 Bergner A, 2005, REV SCI INSTRUM, V76, DOI 10.1063/1.1928427 Born B, 2009, J AM CHEM SOC, V131, P3752, DOI 10.1021/ja808997y Chen JY, 2007, APPL PHYS LETT, V90, DOI 10.1063/1.2748852 He YF, 2008, PHYS REV LETT, V101, DOI 10.1103/PhysRevLett.101.178103 Heugen U, 2006, P NATL ACAD SCI USA, V103, P12301, DOI 10.1073/pnas.0604897103 Jepsen PU, 2007, OPT EXPRESS, V15, P14717, DOI 10.1364/OE.15.014717 Kindt JT, 1996, J PHYS CHEM-US, V100, P10373, DOI 10.1021/jp960141g Knab J, 2006, BIOPHYS J, V90, P2576, DOI 10.1529/biophysj.105.069088 THRANE L, 1995, CHEM PHYS LETT, V240, P330, DOI 10.1016/0009-2614(95)00543-D Xu J, 2006, J CHEM PHYS, V124, DOI 10.1063/1.2151267 Yada H, 2008, CHEM PHYS LETT, V464, P166, DOI 10.1016/j.cplett.2008.09.015 Liang, Wei He, Yunfen George, Deepu Markelz, A. G. Proceedings Paper Conference on Biosensing II Aug 04-06, 2009 San Diego, CA Spie George, Deepu/J-9882-2014 George, Deepu/0000-0003-0021-0705; Markelz, Andrea/0000-0003-0443-4319 1000 20th st, po box 10, bellingham, wa 98227-0010 usa 0277-786x 73970t
Keywords: alanine; dynamics; hydration; lysine; lysozyme; proteins; relaxation; spectroscopy; Terahertz; thz

The role of structure in the protein dynamical transition - He, Yunfen; Markelz, Andrea G (2008 33rd International Conference on Infrared, Millimeter and Terahertz Waves, 2008)

Development of Tagless Biosensors for Detecting the Presence of Pathogens - Markelz, A. G.; Chen, J.-Y.; Knab, J. R.; He, Y.; Ye, S. (Terahertz Frequency Detection and Identification of Materials and Objects, 2007)

Protein dynamical transition in terahertz dielectric response - Markelz, Andrea G.; Knab, Joseph R.; Chen, Jing Yin; He, Yunfen (Chemical Physics Letters, 2007)
The 200K protein dynamical transition is observed for the first time in the terahertz dielectric response. The complex dielectric permittivity ε=ε′+iε″ is determined in the 0.2–2.0THz and 80–294K ranges. ε″ has a linear temperature dependence up to 200K then sharply increases. The low temperature linear dependence in ε″ suggests anharmonicity for temperatures 80K<t<180k, challenging="" the="" assumed="" harmonicity="" below="" 200k.="" temperature="" dependence="" is="" consistent="" with="" thermally="" activated="" sidechain="" motions="" and="" shows="" involved="" in="" dynamical="" transition="" extend="" to="" subpicosecond="" time="" scales.<="" div="">

Terahertz dielectric assay of solution phase protein binding - Chen, J. Y.; Knab, J. R.; Ye, S. J.; He, Y. F.; Markelz, A. G. (Applied Physics Letters, 2007)
The authors demonstrate a method for rapid determination of protein-ligand binding on solution phase samples using terahertz dielectric spectroscopy. Measurements were performed using terahertz time domain spectroscopy on aqueous solutions below the liquid-solid transition for water. Small ligand binding sensitivity was demonstrated using triacetylglucosamine and hen egg white lysozyme with a decrease in dielectric response with binding. The magnitude of the change increases with frequency. (c) 2007 American Institute of Physics.
ISI Document Delivery No.: 179QR Times Cited: 51 Cited Reference Count: 9 Cited References: Balog E, 2004, PHYS REV LETT, V93, DOI 10.1103/PhysRevLett.93.028103 Brucherseifer M, 2000, APPL PHYS LETT, V77, P4049, DOI 10.1063/1.1332415 Chen JY, 2005, PHYS REV E, V72, DOI 10.1103/PhysRevE.72.040901 Fear G, 2007, PHARMACOL THERAPEUT, V113, P354, DOI 10.1016/j.pharmthera.2006.09.001 Heugen U, 2006, P NATL ACAD SCI USA, V103, P12301, DOI 10.1073/pnas.0604897103 Knab J, 2006, BIOPHYS J, V90, P2576, DOI 10.1529/biophysj.105.069088 LEHRER SS, 1967, J BIOL CHEM, V242, P4644 Menikh A, 2004, BIOSENS BIOELECTRON, V20, P658, DOI 10.1016/j.bios.2004.03.006 Xu J, 2006, PROTEIN SCI, V15, P1175, DOI 10.1110/ps.062073506 Chen, Jing-Yin Knab, J. R. Ye, Shuji He, Yunfen Markelz, A. G. Ye, Shuji/B-4479-2010 Markelz, Andrea/0000-0003-0443-4319 53 1 42 Amer inst physics Melville 1077-3118
Keywords: dynamics; lysozyme; Physics; spectroscopy; water

Terahertz measurements of protein relaxational dynamics - Knab, Joseph R; Chen, Jing-Yin; He, Yunfen; Markelz, Andrea G (Proceedings of the IEEE, 2007)

Protein conformational dynamics measured with terahertz time domain spectroscopy - Knab, Joseph R; Chen, Jing-Yin; Ye, Shuji; He, Yunfen; Markelz, Andrea G (2006 Joint 31st International Conference on Infrared Millimeter Waves and 14th International Conference on Teraherz Electronics, 2006)

Using terahertz spectroscopy as a protein binding assay - Chen, J.-Y.; Knab, J. R.; Ye, S.; He, Y.; Markelz, A. G. (Advanced Biomedical and Clinical Diagnostic Systems IV, 2006)
The vibrational modes corresponding to protein tertiary structural motion lay in the far infrared or terahertz frequency range. These collective large scale motions depend on global structure and thus will necessarily be perturbed by ligand binding events. We discuss the use of terahertz dielectric spectroscopy to measure these vibrational modes and the sensitivity of the technique to changes in protein conformation, oxidation state and environment. A challenge of applying this sensitivity as a spectroscopic assay for ligand binding is the sensitivity of the technique to both bulk water and water bound to the protein. This sensitivity can entirely obscure the signal from the protein or protein-ligand complex itself, thus necessitating sophisticated sample preparation making the technique impractical for industrial applications. We discuss methods to overcome this background and demonstrate how terahertz spectroscopy can be used to quickly assay protein binding for proteomics and pharmaceutical research.

Terahertz measurements of the Photoactive Protein Bacteriorhodopsin mutant D96N: M and P states - Chen, C.-Y.; Knab, J. R.; Cerne, J.; Hillebrecht, J. R.; Birge, R. R.; Markelz, A. G. (Mater. Res. Soc. Symp., 2004)
We use terahertz (THz) spectroscopy as a biomaterials characterization tool. Previously we have shown a strong contrast between the THz dielectric response for wild type (WT) and D96N mutant of bacteriorhodopsin. In those studies we observed a large increase in the THz absorbance of WT with excitation to thermally captured photo-intermediates whereas no such increase in absorbance was observed for the mutant D96N. These results suggest that the THz response is sensitive to structural changes and relative flexibility of biomolecules. However the photo-intermediate populations of the WT and D96N samples were not equivalent in those measurements. While the WT samples had relaxed (bR), M and P state intermediates present, the D96N samples had only bR and M states. Here we present terahertz absorbance measurements of D96N as a function of M and P state populations at room temperature. The THz response is constant for intermediate states populations up to 23% M state and up to 30% P state. These results verify that there is a fundamental difference in the conformational dynamics as measured by THz dielectric response for a single residue mutation.

Protein flexibility and conformational state: A comparison of collective vibrational modes of wild-type and D96N bacteriorhodopsin - Whitmire, S. E.; Wolpert, D.; Markelz, A. G.; Hillebrecht, J. R.; Galan, J.; Birge, R. R. (Biophysical Journal, 2003)
Far infrared ( FIR) spectral measurements of wild-type (WT) and D96N mutant bacteriorhodopsin thin films have been carried out using terahertz time domain spectroscopy as a function of hydration, temperature, and conformational state. The results are compared to calculated spectra generated via normal mode analyses using CHARMM. We find that the FIR absorbance is slowly increasing with frequency and without strong narrow features over the range of 2-60 cm(-1) and up to a resolution of 0.17 cm(-1). The broad absorption shifts in frequency with decreasing temperature as expected with a strongly anharmonic potential and in agreement with neutron inelastic scattering results. Decreasing hydration shifts the absorption to higher frequencies, possibly resulting from decreased coupling mediated by the interior water molecules. Ground-state FIR absorbances have nearly identical frequency dependence, with the mutant having less optical density than the WT. In the M state, the FIR absorbance of the WT increases whereas there is no change for D96N. These results represent the first measurement of FIR absorbance change as a function of conformational state.
ISI Document Delivery No.: 705ZZ Times Cited: 117 Cited Reference Count: 55 Cited References: AUSTIN RH, 1975, BIOCHEMISTRY-US, V14, P5355, DOI 10.1021/bi00695a021 Birge RR, 1996, J PHYS CHEM-US, V100, P9990, DOI 10.1021/jp953669e BOUSCHE O, 1992, PHOTOCHEM PHOTOBIOL, V56, P1085, DOI 10.1111/j.1751-1097.1992.tb09732.x BROOKS BR, 1983, J COMPUT CHEM, V4, P187, DOI 10.1002/jcc.540040211 BROOKS BR, 1995, J COMPUT CHEM, V16, P1522, DOI 10.1002/jcc.540161209 Brooks CL, 1988, PROTEINS THEORETICAL Brucherseifer M, 2000, APPL PHYS LETT, V77, P4049, DOI 10.1063/1.1332415 Chen Q, 2001, J OPT SOC AM B, V18, P823, DOI 10.1364/JOSAB.18.000823 DENCHER NA, 1989, P NATL ACAD SCI USA, V86, P7876, DOI 10.1073/pnas.86.20.7876 Der A, 2001, BIOCHEMISTRY-MOSCOW+, V66, P1234, DOI 10.1023/A:1013179101782 Diehl M, 1997, BIOPHYS J, V73, P2726, DOI 10.1016/S0006-3495(97)78301-2 DOSTER W, 1989, NATURE, V337, P754, DOI 10.1038/337754a0 FERRAND M, 1993, P NATL ACAD SCI USA, V90, P9668, DOI 10.1073/pnas.90.20.9668 GENZEL L, 1984, SPECTROSCOPY BIOL MO, P609 GRISCHKOWSKY D, 1991, OSA PROC, V9, P9 Guilbert C, 1996, CHEM PHYS, V204, P327, DOI 10.1016/0301-0104(95)00293-6 Han PY, 2000, OPT LETT, V25, P242, DOI 10.1364/OL.25.000242 Hinsen K, 1998, PROTEINS, V33, P417, DOI 10.1002/(SICI)1097-0134(19981115)33:3<417::AID-PROT10>3.0.CO;2-8 JANEZIC D, 1995, J COMPUT CHEM, V16, P1543, DOI 10.1002/jcc.540161210 Kusnetzow A, 1999, BIOPHYS J, V76, P2370, DOI 10.1016/S0006-3495(99)77394-7 Lanyi JK, 1999, INT REV CYTOL, V187, P161, DOI 10.1016/S0074-7696(08)62418-3 Lanyi JK, 2001, TRENDS BIOTECHNOL, V19, P140, DOI 10.1016/S0167-7799(01)01576-1 LINDSAY SM, 1988, BIOPOLYMERS, V27, P1015, DOI 10.1002/bip.360270610 Lisy V, 1997, J BIOMOL STRUCT DYN, V14, P517, DOI 10.1080/07391102.1997.10508150 LONGBOTTOM C, 2002, POTENTIAL USES TERAH Luecke H, 1999, SCIENCE, V286, P255, DOI 10.1126/science.286.5438.255 Luecke H, 1999, J MOL BIOL, V291, P899, DOI 10.1006/jmbi.1999.3027 MacKerell AD, 1998, J PHYS CHEM B, V102, P3586, DOI 10.1021/jp973084f Markelz AG, 2000, CHEM PHYS LETT, V320, P42, DOI 10.1016/S0009-2614(00)00227-X MCINTOSH AR, 1991, BIOPHYS J, V60, P1, DOI 10.1016/S0006-3495(91)82025-2 MOUAWAD L, 1993, BIOPOLYMERS, V33, P599, DOI 10.1002/bip.360330409 Mouawad L, 1996, J MOL BIOL, V258, P393, DOI 10.1006/jmbi.1996.0257 Nagel M, 2002, APPL PHYS LETT, V80, P154, DOI 10.1063/1.1428619 Oesterhelt D, 1974, Methods Enzymol, V31, P667 Palmo K, 1998, J COMPUT CHEM, V19, P754, DOI 10.1002/(SICI)1096-987X(199805)19:7<754::AID-JCC6>3.0.CO;2-P PERAHIA D, 1995, COMPUT CHEM, V19, P241, DOI 10.1016/0097-8485(95)00011-G Person W.B., 1982, VIBRATIONAL INTENSIT Polavarapu P. L., 1998, VIBRATIONAL SPECTRA POWELL JW, 1991, J MOL STRUCT, V247, P107, DOI 10.1016/0022-2860(91)87067-R POWELL JW, 1987, PHYS REV A, V35, P3929, DOI 10.1103/PhysRevA.35.3929 Ren L, 2001, BIOCHEMISTRY-US, V40, P13906, DOI 10.1021/bi0116487 ROITBERG A, 1995, SCIENCE, V268, P1319, DOI 10.1126/science.7539156 Sass HJ, 1997, EMBO J, V16, P1484, DOI 10.1093/emboj/16.7.1484 Stuart JA, 1996, BIOMEMBR A&B, V2, P33 Urabe H, 1998, BIOPHYS J, V74, P1533, DOI 10.1016/S0006-3495(98)77865-8 VARO G, 1983, BIOPHYS J, V43, P47, DOI 10.1016/S0006-3495(83)84322-7 Walther M, 2000, CHEM PHYS LETT, V332, P389, DOI 10.1016/S0009-2614(00)01271-9 WEIDLICH T, 1990, BIOPOLYMERS, V30, P477, DOI 10.1002/bip.360300324 WEIDLICH T, 1990, J BIOMOL STRUCT DYN, V8, P139, DOI 10.1080/07391102.1990.10507795 WEIDLICH T, 1987, BIOPOLYMERS, V26, P439, DOI 10.1002/bip.360260310 WEIDLICH T, 1988, J PHYS CHEM-US, V92, P6475 WITTLIN A, 1986, PHYS REV A, V34, P493, DOI 10.1103/PhysRevA.34.493 Woolard DL, 1997, J APPL TOXICOL, V17, P243, DOI 10.1002/(SICI)1099-1263(199707)17:4<243::AID-JAT436>3.0.CO;2-6 Xie AH, 2002, PHYS REV LETT, V88, DOI 10.1103/PhysRevLett.88.018102 Zaccai G, 2000, SCIENCE, V288, P1604, DOI 10.1126/science.288.5471.1604 Whitmire, SE Wolpert, D Markelz, AG Hillebrecht, JR Galan, J Birge, RR Markelz, Andrea/0000-0003-0443-4319 NATIONAL INSTITUTE OF GENERAL MEDICAL SCIENCESUnited States Department of Health & Human ServicesNational Institutes of Health (NIH) - USANIH National Institute of General Medical Sciences (NIGMS) [R01GM034548, R01GM034548, R01GM034548, R01GM034548, R01GM034548, R01GM034548, R01GM034548, R01GM034548, R01GM034548, R01GM034548, R01GM034548, R01GM034548, R01GM034548, R01GM034548, R01GM034548, R01GM034548, R01GM034548, R01GM034548, R01GM034548, R01GM034548, R01GM034548, R01GM034548, R01GM034548, R01GM034548] Funding Source: NIH RePORTER; NIGMS NIH HHSUnited States Department of Health & Human ServicesNational Institutes of Health (NIH) - USANIH National Institute of General Medical Sciences (NIGMS) [R01 GM034548, R01 GM034548-15] Funding Source: Medline 122 3 31 Cell press Cambridge 1542-0086
Keywords: angstrom resolution; Biophysics; dna; films; frequency; harmonic-analysis; inelastic neutron-scattering; large systems; mixed basis; normal-modes; purple membranes; structural-changes; transform infrared-spectroscopy

Ultrafast THz spectroscopy of photoactive biomolecules - Chen, J.-Y.; Whitmire, S. E.; Markelz, A. G.; Hillebrecht, J. R.; Birge, R. R. (Ultrafast Phenomena in Semiconductors VII, 2003)

THz time domain spectroscopy of biomolecular conformational modes - Markelz, Andrea; Whitmire, Scott; Hillebrecht, Jay; Birge, Robert (Physics in Medicine & Biology, 2002)

Terahertz Time domain spectroscopy of the M intermediate state of Bacteriorhodopsin - Whitmire, S.; Markelz, A. G.; Hillebrecht, J. R.; Birge, R. R. (Proceedings of the 26th International Conference on Infrared and Millimeter Waves, 2001)

Pulsed terahertz spectroscopy of DNA, bovine serum albumin and collagen between 0.1 and 2.0 THz - Markelz, A. G.; Roitberg, A.; Heilweil, E. J. (Chemical Physics Letters, 2000)
We report the first use of pulsed terahertz spectroscopy to examine low-frequency collective vibrational modes of biomolecules. Broadband absorption increasing with frequency was observed for lyophilized powder samples of calf thymus DNA, bovine serum albumin and collagen in the 0.06-2.00 THz (2-67 cm(-1)) frequency range, suggesting that a large number of the low-frequency collective modes for these systems are IR active. Transmission measurements at room temperature showed increasing FIR absorption with hydration and denaturing. (C) 2000 published by Elsevier Science B.V. All rights reserved.
ISI Document Delivery No.: 299RG Times Cited: 561 Cited Reference Count: 24 Cited References: Cai Y, 1998, APPL PHYS LETT, V73, P444, DOI 10.1063/1.121894 CARTER DC, 1994, ADV PROTEIN CHEM, V45, P153 Chen EF, 1998, BIOCHEMISTRY-US, V37, P5589, DOI 10.1021/bi972369f CHEVILLE RA, 1995, OPT LETT, V20, P1646, DOI 10.1364/OL.20.001646 FENG Y, 1991, PHYS REV A, V43, P1049, DOI 10.1103/PhysRevA.43.1049 Fraser R.D.B., 1973, CONFORMATION FIBROUS Frushour B., 1975, ADV INFRARED RAMAN S, V1 GENZEL L, 1984, SPECTROSCOPY BIOL MO, P609 GRIEBENOW K, 1995, P NATL ACAD SCI USA, V92, P10969, DOI 10.1073/pnas.92.24.10969 HAYWARD S, 1995, ANNU REV PHYS CHEM, V46, P223, DOI 10.1146/annurev.pc.46.100195.001255 KATZENELLENBOGE.N, 1992, ULTRA WIDEBAND SHORT Kindt JT, 1996, J PHYS CHEM-US, V100, P10373, DOI 10.1021/jp960141g LINDSAY SM, 1988, BIOPOLYMERS, V27, P1015, DOI 10.1002/bip.360270610 Lisy V, 1997, J BIOMOL STRUCT DYN, V14, P517, DOI 10.1080/07391102.1997.10508150 Markelz AG, 1998, APPL PHYS LETT, V72, P2229, DOI 10.1063/1.121329 Nossal R. J., 1991, MOL CELL BIOPHYSICS POWELL JW, 1987, PHYS REV A, V35, P3929, DOI 10.1103/PhysRevA.35.3929 POWELL JW, 1991, J MOL STRUCT, V247, P119 ROITBERG A, 1995, SCIENCE, V268, P1319, DOI 10.1126/science.7539156 WEIDLICH T, 1990, BIOPOLYMERS, V30, P477, DOI 10.1002/bip.360300324 WEIDLICH T, 1990, J BIOMOL STRUCT DYN, V8, P139, DOI 10.1080/07391102.1990.10507795 WITTLIN A, 1986, PHYS REV A, V34, P493, DOI 10.1103/PhysRevA.34.493 YOUNG L, 1990, PHYS REV A, V41, P7020, DOI 10.1103/PhysRevA.41.7020 ZHUANG W, 1990, PHYS REV A, V41, P7033, DOI 10.1103/PhysRevA.41.7033 Markelz, AG Roitberg, A Heilweil, EJ Roitberg, Adrian/A-2378-2009 Markelz, Andrea/0000-0003-0443-4319 598 7 235 Elsevier science bv Amsterdam
Keywords: b-dna; Chemistry; films; modes; Physics; proteins

Temperature-dependent terahertz output from semi-insulating GaAs photoconductive switches - Markelz, A. G.; Heilweil, E. J. (Applied Physics Letters, 1998)
The temperature dependence of the terahertz (THz) output power and spectra from biased photoconductive switches was measured for several antenna gap widths and applied biases. The spectrally integrated THz output had a nonmonotonic temperature dependence in all cases with the value increasing by a factor of 3 from room temperature to 150 K for low biases and 100 K at high biases. An abrupt decrease in output power occurs below 90 K, and the spectrum shifts to lower frequencies as the temperature is lowered. (C) 1998 American Institute of Physics.
ISI Document Delivery No.: ZK775 Times Cited: 22 Cited Reference Count: 21 Cited References: Brener I, 1996, OPT LETT, V21, P1924, DOI 10.1364/OL.21.001924 BRORSON SD, 1994, APPL PHYS LETT, V64, P2385, DOI 10.1063/1.111622 CHEVILLE RA, 1995, OPT LETT, V20, P1646, DOI 10.1364/OL.20.001646 Flanders BN, 1996, J PHYS CHEM-US, V100, P11824, DOI 10.1021/jp960953c Haran G, 1997, CHEM PHYS LETT, V274, P365, DOI 10.1016/S0009-2614(97)00705-7 HU BB, 1990, APPL PHYS LETT, V57, P2629, DOI 10.1063/1.103829 HU BB, 1995, PHYS REV LETT, V74, P1689, DOI 10.1103/PhysRevLett.74.1689 Jepsen PU, 1996, J OPT SOC AM B, V13, P2424, DOI 10.1364/JOSAB.13.002424 KATZENELLENBOGE.N, 1992, ULTRA WIDEBAND SHORT Kindt JT, 1996, J PHYS CHEM-US, V100, P10373, DOI 10.1021/jp960141g Nahata A, 1996, APPL PHYS LETT, V69, P2321, DOI 10.1063/1.117511 NUSS MC, 1987, PHYS REV LETT, V58, P2355, DOI 10.1103/PhysRevLett.58.2355 NUSS MC, 1991, PHYS REV LETT, V66, P3305, DOI 10.1103/PhysRevLett.66.3305 PARKS B, 1995, PHYS REV LETT, V74, P3265, DOI 10.1103/PhysRevLett.74.3265 RALPH SE, 1992, PHOTO INDUCED SPACE, V261 RODRIGUEZ G, 1994, OPT LETT, V19, P1194 SAETA PN, 1992, APPL PHYS LETT, V60, P1477, DOI 10.1063/1.107276 WANG HH, 1993, J ELECTRON MATER, V22, P1461, DOI 10.1007/BF02649999 Wang S, 1989, FUNDAMENTALS SEMICON ZHANG XC, 1990, APPL PHYS LETT, V56, P1011, DOI 10.1063/1.102601 ZHANG XC, 1994, APPL PHYS LETT, V64, P622, DOI 10.1063/1.111069 Markelz, AG Heilweil, EJ Markelz, Andrea/0000-0003-0443-4319 22 6 Amer inst physics Woodbury
Keywords: domain; generation; Physics; pulses; semiconductor surfaces; transmission spectroscopy

Undressing a collective intersubband excitation in a quantum well - Craig, K.; Galdrikian, B.; Heyman, J. N.; Markelz, A. G.; Williams, J. B.; Sherwin, M. S.; Campman, K.; Hopkins, P. F.; Gossard, A. C. (Physical Review Letters, 1996)
We have experimentally measured the 1-2 intersubband absorption in a single 40 nm wide modulation-doped Al0.3Ga0.7As/GaAs square quantum well as a function of frequency, intensity, and charge density. The low-intensity depolarization-shifted absorption occurs near 80 cm(-1) (10 meV or 2.4 THz), nearly 30% higher than the intersubband spacing. At higher intensities, the absorption peak shifts to lower frequencies. Our data are in good agreement with a theory proposed by Zaluzny, which attributes the redshift to a reduction in the depolarization shift as the excited subband becomes populated.
Sherwin, Mark S/Q-4762-2017 Sherwin, Mark S/0000-0002-3869-1893; Markelz, Andrea/0000-0003-0443-4319 78

NONLINEAR QUANTUM DYNAMICS IN SEMICONDUCTOR QUANTUM-WELLS - Sherwin, M. S.; Craig, K.; Galdrikian, B.; Heyman, J.; Markelz, A.; Campman, K.; Fafard, S.; Hopkins, P. F.; Gossard, A. (Physica D-Nonlinear Phenomena, 1995)
We discuss recent measurements of the nonlinear response of electrons in wide quantum wells driven by intense electromagnetic radiation at terahertz frequencies. The theme is the interplay of quantum mechanics, strong periodic driving, the electron-electron interaction and dissipation. We discuss harmonic generation from an asymmetric double quantum well in which the effects of dynamic screening are important. Measurements and theory are found to be in good agreement. We also discuss intensity-dependent absorption in a 400 Angstrom square quantum well. A new nonlinear quantum effect occurs, in which the frequency at which electromagnetic radiation is absorbed shifts to the red with increasing intensity. The preliminary experimental results are in agreement with a theory by Zaluzny, in which the source of the nonlinearity is the self-consistent potential in the Hartree approximation for the electron dynamics.
Sherwin, Mark S/Q-4762-2017 Sherwin, Mark S/0000-0002-3869-1893; Markelz, Andrea/0000-0003-0443-4319 14th Annual International Conference of the Center-for-Nonlinear-Studies - Quantum Complexity in Mesoscopic Systems May 16-20, 1994 Los alamos, nm Ctr nonlinear studies 34

RESONANT-ENERGY RELAXATION OF TERAHERTZ-DRIVEN 2-DIMENSIONAL ELECTRON GASES - Asmar, N. G.; Markelz, A. G.; Gwinn, E. G.; Cerne, J.; Sherwin, M. S.; Campman, K. L.; Hopkins, P. F.; Gossard, A. C. (Physical Review B, 1995)
Sherwin, Mark S/Q-4762-2017 Sherwin, Mark S/0000-0002-3869-1893; Markelz, Andrea/0000-0003-0443-4319 119

Terahertz grid frequency doublers - Chiao, Jung-Chih; Markelz, Andrea; Li, Yongjun; Hacker, Jonathan; Crowe, Thomas; Allen, James; Rutledge, David (Proc. Sixth Intl. Symp. Space Terahertz Tech, 1995)

DC TRANSPORT IN INTENSE, INPLANE TERAHERTZ ELECTRIC-FIELDS IN AL(X)GA(1-X)AS HETEROSTRUCTURES AT 300-K - Asmar, N. G.; Markelz, A. G.; Gwinn, E. G.; Hopkins, P. F.; Gossard, A. C. (Solid-State Electronics, 1994)
We report 300 K studies of the dependence of the in-plane, d.c. conductivity, sigma(d.c.) (E(omega)), of a quasi 2D electron gas on the amplitude E(omega) and frequency of intense, far-infrared fields (omega/2pi = 0.24-3.5 THz). We measure sigma(d.c.) (E(omega) parallel-to E(d.c.)), where E(d.c.) is a small sensing field, and observe a monotonic decrease in sigma(d.c.) with increasing E(omega). Although a simple scaling ansatz collapses the measured sigma(d.c.) (E(omega)) data onto a single curve for frequencies from 0.25-3.45 THz (at low to moderate scaled fields), the decrease in conductivity is substantially more rapid than expected from comparison to similar data taken by Masselink et al. [Solid-St. Electron. 31, 337 (1988)] at 35 GHz. We tentatively attribute this difference to effects of a high-frequency modulation in the electron temperature.
Markelz, Andrea/0000-0003-0443-4319 6th International Conference on Modulated Semiconductor Structures Aug 23-27, 1993 Garmisch partenkir, germany Tech univ munchen, walter schottky inst 1

ENERGY RELAXATION AT THZ FREQUENCIES IN ALXGA1-XAS HETEROSTRUCTURES - Asmar, N. G.; Markelz, A. G.; Gwinn, E. G.; Hopkins, P. F.; Gossard, A. C. (Semiconductor Science and Technology, 1994)
We report 4.2 K studies of the dependence of the in-plane, DC conductivity of a quasi 2D electron gas on the amplitude E(omega) of applied fields with frequencies from 0.25 THz to 3.5 THz. We analyse the dependence of sigma(DC) on E(omega) assuming that electron-optical phonon scattering dominates energy relaxation, that the absorbed power has a Drude form and that the electron distribution is thermal. This simple analysis is self-consistent: Arrhenius plots of the estimated energy loss rate have a slope near -homega(LO)BAR/k(B) for all frequencies, as expected for energy loss by optical phonon emission. We find that the effective energy relaxation time tau(epsilon) varies with the frequency of the applied field, from tau(epsilon) approximately 4 ps at 0.34 THz to tau(epsilon) approximately 0.3 ps at 3.45 THz. This may indicate a frequency-dependent form for the hot-phonon distribution.
Markelz, Andrea/0000-0003-0443-4319 S 8th International Conference on Hot Carriers in Semiconductors Aug 16-20, 1993 Oxford univ, oxford, england Sci & engn res council; royal soc; brit council; oxford univ 2

Far-infrared harmonic generation from semiconductor heterostructures - Markelz, A.G.; Gwinn, E. G.; Sherwin, M. S.; Heyman, J. N.; Nguyen, C.; Kroemer, H. (SPIE Proceedings, 1994)

FAR-INFRARED SATURATION SPECTROSCOPY OF A SINGLE SQUARE-WELL - Craig, K.; Felix, C. L.; Heyman, J. N.; Markelz, A. G.; Sherwin, M. S.; Campman, K. L.; Hopkins, P. F.; Gossard, A. C. (Semiconductor Science and Technology, 1994)
We have performed saturation spectroscopy measurements of the lowest intersubband transition in a single 400 angstrom GaAs/Al0.3Ga0.7As modulation-doped square quantum well. We couple intense tunable far-infrared radiation from the Santa Barbara free electron laser into our sample using an edge-coupling technique and measure absorption as a function of frequency and intensity. Saturation and frequency shifts in the absorption line are clearly observed. We attribute the frequency shifts to reductions in the many-body depolarization shift. From our preliminary measurements, we estimate the intersubband relaxation time to be 600 ps to within a factor of three.
Sherwin, Mark S/Q-4762-2017 Sherwin, Mark S/0000-0002-3869-1893; Markelz, Andrea/0000-0003-0443-4319 S 8th International Conference on Hot Carriers in Semiconductors Aug 16-20, 1993 Oxford univ, oxford, england Sci & engn res council; royal soc; brit council; oxford univ 31

PROBING TERAHERTZ DYNAMICS IN SEMICONDUCTOR NANOSTRUCTURES WITH UCSB FREE-ELECTRON LASERS - Allen, S. J.; Craig, K.; Felix, C. L.; Guimaraes, P.; Heyman, J. N.; Kaminski, J. P.; Keay, B. J.; Markelz, A. G.; Ramian, G.; Scott, J. S.; Sherwin, M. S.; Campman, K. L.; et al. (Journal of Luminescence, 1994)
The UCSB free-electron lasers provide kilowatts of continuously tunable radiation from 120 GHz to 4.8 THz. They have the most impact on terahertz science and technology that require a tunable, high power source to explore non-linear dynamics or that sacrifice incident power to recover the linear response of systems with very small cross-section. We describe three experiments that demonstrate the utility of these lasers in experiments on the terahertz dynamics of semiconductor nanostructures: (i) terahertz dynamics of resonant tunneling diodes, (ii) saturation spectroscopy of quantum wells and (iii) photon-assisted tunneling in superlattices.
Sherwin, Mark S/Q-4762-2017; Guimaraes, Paulo Sergio Soares/B-6918-2012 Sherwin, Mark S/0000-0002-3869-1893; Guimaraes, Paulo Sergio Soares/0000-0002-0113-2641; Markelz, Andrea/0000-0003-0443-4319 1993 International Conference on Luminescence (ICL 93) Aug 09-13, 1993 Univ connecticut, storrs, ct Univ connecticut; opt soc amer; amer phys soc; ieee, laser & electro opt soc; int union pure & appl phys; int sci fdn; univ connecticut res fdn 3

Far-infrared nonlinear response of electrons in semiconductor nanostructures - Sherwin, M. S.; Asmar, N. G.; Bewley, W. W.; Craig, K.; Felix, C. L.; Galdrikian, B.; Gwinn, E. G.; Markelz, A.G.; Gossard, A. C.; Hopkins, P. F.; Sundaram, M.; Birnir, B. (SPIE Proceedings, 1993)

Site-selective oxygen-isotope substitution in YBa2Cu3O7−δ - Morris, D. E.; Markelz, A. G.; Wei, J. Y. T.; Huitgren, C. T.; Nickel, J. H.; Hamilton, J. C.; McCarty, K. F. (Physical Review B, 1991)
We report selective substitution of oxygen-18 and oxygen-16 isotopes into the inequivalent oxygen lattice sites in YBa2Cu3O7−δ. The technique involves gas-phase diffusion and exploits the site dependence of diffusion rates. The CuO2-plane [O(2),O(3)] sites of YBa2Cu3O7−δ can be filled with 18O while the apical [O(4)] and CuO-chain sites [O(1)] contain 16O (the opposite distribution can also be made). The site-selective isotope occupation has been confirmed by Raman spectroscopy. Our method will permit experiments to determine the contributions of the different oxygen sites to the isotope effect, in order to locate the pairing interaction within the unit cell.

8 NEW HIGH-TEMPERATURE SUPERCONDUCTORS WITH THE 1-2-4 STRUCTURE - Morris, D. E.; Nickel, J. H.; Wei, J. Y. T.; Asmar, N. G.; Scott, J. S.; Scheven, U. M.; Hultgren, C. T.; Markelz, A. G.; Post, J. E.; Heaney, P. J.; Veblen, D. R.; Hazen, R. M. (Physical Review B, 1989)
Scheven, Ulrich/D-7582-2013 Markelz, Andrea/0000-0003-0443-4319; Scheven, Ulrich/0000-0001-8111-0081 B 241

OXYGEN CONCENTRATION EFFECT ON TC OF THE BI-CA-SR-CU-O SUPERCONDUCTOR - Morris, D. E.; Hultgren, C. T.; Markelz, A. M.; Wei, J. Y. T.; Asmar, N. G.; Nickel, J. H. (Physical Review B, 1989)
A 155